THE CONCEPT AND THE HISTORY OF ADVERTISEMENT (Academicia Globe: Inderscience Research, 2024)
In the present article, it is attempted to conduct a research concerning the concept and the history of advertising and analyzed it by using a several research methods. The main aim of this research paper is to study through observations, analyses and examinations of peculiar types of concepts and the history of ads. The object of this article is English and Uzbek advertisements whereas the subject matter is the history of advertisement.